2019
DOI: 10.3390/su11113206
|View full text |Cite
|
Sign up to set email alerts
|

How to Save Bike-Sharing: An Evidence-Based Survival Toolkit for Policy-Makers and Mobility Providers

Abstract: A new mobility ethos is needed for cities looking to overcome the problems that have been accumulated for decades by a transport paradigm that prioritises automobiles over people. Bike-sharing, a measure promoting voluntary travel behaviour change, could be part of a refined toolbox that will help in forging this new ethos. Despite a rapid emergence during the last handful of years, as evidenced by 1956 operational local schemes and approximately 15,254,400 self-service public use bicycles across the world, bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 58 publications
5
48
0
1
Order By: Relevance
“…The study conducted in Belgium also found that having significant others to cycle with (accompany effect) or without (modeling effect) could both predict cycling for commute [ 23 ]. Indeed, literature suggests one of the keys to a successful bike share is to encourage people to adopt a positive attitude towards these bikes [ 44 ]. Research also recommends using multistage behavior change theory to align interventions with user readiness to turning intentions to use bike share into actions [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study conducted in Belgium also found that having significant others to cycle with (accompany effect) or without (modeling effect) could both predict cycling for commute [ 23 ]. Indeed, literature suggests one of the keys to a successful bike share is to encourage people to adopt a positive attitude towards these bikes [ 44 ]. Research also recommends using multistage behavior change theory to align interventions with user readiness to turning intentions to use bike share into actions [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…As dockless bike share systems increase users’ access to service and hold promise for offering equitable access to bike share, it is important to understand the impact of the emergence of dockless bike share services [ 4 , 48 ]. When bike share system data can be linked to users’ survey data, researchers can further extend this study to examine the effects of socio-ecological predictors on travel characteristics, such as travel distance and travel time [ 44 , 49 ]. In addition, the data were collected using online surveys.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars began to pay attention to the practical problems that FFBS has to face, such as parking disorder and unbalanced distribution of bikes. Nikitas [14] pointed out that oversupply is a fatal reason for OFO's launch failure in the UK. Similarly, unlimited bikes supply, unbalanced parking, and parking disorder resulted in common challenges to the FFBS in China, which became worse around subway stations [6,15].…”
Section: Study On Bike-sharing and Ffbsmentioning
confidence: 99%
“…In addition to those benefits concerning traffic efficiency and environmental sustainability, a bicycle-sharing system also supports multimodal transport connections by acting as a "last mile" connection to public transport [21]. In recent years, with the rapid implement of bicycle-sharing systems across the globe, a growing interest has been drawn on the application of bicycle-sharing data [21][22][23]. Caulfield et al examined the usage patterns of bicycle-sharing in Cork, Ireland, and found that bicycle-sharing usage was associated with weather condition and travel distance [24].…”
Section: Introductionmentioning
confidence: 99%
“…Bakogiannis et al analysed the efficiency of a bicycle-sharing system in Rethimno, Greece, and reported that the bicycle-sharing system was primarily used for short distance trips, and traffic safety concern coupled with service limitation were the two factors affecting bicycle-sharing usage [25]. Most studies focus on the bicycle-sharing usage pattern allied with its corresponding influence factors [20][21][22][23]26,27], less often paying attention to the interaction between the bicycle-sharing users and urban dynamics. It follows that if we attempt to encourage more bicycle usage as a way to progress towards a more sustainable transport system, there is a compelling need to investigate the intra-city movement of cyclists as well as the urban dynamics characterised by those cyclists.…”
Section: Introductionmentioning
confidence: 99%